A Qualitative Exploration of Parental Perceptions Regarding Children's Sun Exposure, Sun Protection, and Sunburn - Thoonen, Karlijn; van Osch, Liesbeth; Drittij, Rowan; de Vries, Hein; Schneider, Francine (Frontiers in Public Health, 2021)
Sun protection among children is of utmost importance since sunburn in early life is a major risk factor for skin cancer development. Because parents play a vital role in enhancing sun safety among children, this study explored parental perceptions concerning sun exposure, sun protection behaviors, and sunburn in children. Additionally, the context in which children experience sunburn in order to assist the development, optimization, and targeting of sun safety interventions for parents is revealed. A qualitative study design, using a semi-structured interview guide addressing several themes (e.g. sun exposure, sun protection, and sunburn experiences), was used. Data were collected in the Netherlands in the fall of 2019. Parents were recruited via purposive sampling at schools, youth services centers, and social media. Execution, transcription, and coding of the interviews was done by two researchers, using the qualitative analyzing program Nvivo (interrater reliability of d =.84). In total, 26 interviews were performed (n=17 mothers, n=17 daughters, aged between 4 -11 years). Parental perceptions and recall of their child’s lifetime sunburn were frequent, even though all parents reported using at least one sun protection measure during sun exposure situations and parents seemed often unaware of their child’s sunburn. Moreover, parents reported an overreliance on sunscreen, often failing to adequately protect their children’s skin. Water-related activities, a lack of shade, and misconceptions regarding UV-index were often related to sunburn. In addition, unexpected sun exposure or longer exposure duration than initially planned were reported as challenging situations. The majority of parents had positive perceptions regarding tanned skin for both themselves as for children. This study provides directions for skin cancer prevention efforts targeted at both parents and their children. Since a lack of knowledge regarding sufficient sun protection measures and sunburn occurrence in various situations was reported, educational efforts are warranted. Additionally, focusing on clothing, shade-seeking, and adequate sunscreen use is recommended to increase children’s sun safety. By intervening in the physical environment as well (e.g. providing shady areas), sun protection barriers can be reduced. Lastly, the general positive attitude towards tanned skin evident in this study is certainly worthy of attention in future interventions.